Increasing nitrogen addition rates suppressed long-term litter decomposition in a temperate meadow steppe. (8th August 2022) - Zheng, Pei; Zhao, Ruonan; Jiang, Liangchao; Yang, Guojiao; Wang, Yinliu; Wang, Ruzhen; Han, Xingguo; Ning, Qiushi
Abstract: Plant litter decomposition is critical for the carbon (C) balance and nutrient turnover in terrestrial ecosystems, and is sensitive to the ongoing anthropogenic biologically nitrogen (N) input. Previous studies evaluating the N effect on litter decomposition relied mostly on short-term experiments (<2 years), which may mask the real N effect on litter decomposition. Therefore, long-lasting experiments are imperative for the overall evaluation of the litter decomposition dynamics under N enrichment. We conducted a relative long-term (4-year) N-addition experiment with N levels ranging from 0 to 50 g N m −2 yr −1 to identify the potential abiotic and biotic factors in regulating the decomposition process of litterfall from the dominant species Leymus chinensis . The results showed a consistent decrease of decomposition rate with increasing N-addition rates, providing strong evidence in support of the inhibitory effect of N addition on decomposition. The N-induced alterations in soil environment (acidification and nutrient stoichiometry), microbial activity (microbial biomass and enzyme activity), changes of litter quality (residual lignin and nutrient content) and plant community (aboveground productivity and species richness) jointly contributed to the lowered decomposition. During the whole decomposition process, the changes of litter quality, including accumulation of lignin and the concentrations of nutrient, were mainly driven by the soil and microbial activity in this N-enriched environment. The findings help clarify how increasing N input rates affect long-term litter decomposition, and advance the mechanistic understanding of the linkages between ecosystem N enrichment and terrestrial C cycling.